2019
DOI: 10.1002/jrs.5612
|View full text |Cite
|
Sign up to set email alerts
|

Orange for gold? Arsenic sulfide glass on the V&A Leman Album

Abstract: The so‐called Leman Album comprises over 90 designs for woven silks drawn and coloured in the early 18th century by James Leman, a designer and weaver operating in Spitalfields, East London. The designs are characterised by a very broad palette, which was investigated at the Victoria and Albert Museum using exclusively non‐invasive techniques. Notably, a bright and vibrant orange material was very popular with Leman, who used it extensively. X‐ray fluorescence tests showed that arsenic and sulfur were the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…5). And it was still Raman microscopy which helped identifying and characterizing arsenic glass used as a pigment (Vermeulen et al 2015;Vermeulen and Leona 2019;Burgio et al 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). And it was still Raman microscopy which helped identifying and characterizing arsenic glass used as a pigment (Vermeulen et al 2015;Vermeulen and Leona 2019;Burgio et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Japanese woodblock prints have been studied extensively and were shown to contain synthetic arsenic sulfides (Vermeulen and Leona 2019). Synthetic arsenic pigments were also detected in a French rococo oil painting and Japanese leather paper , and arsenic sulfide glass was found in many early 18 th -century designs for woven silk made by designer and weaver James Leman in London (Burgio et al 2019).…”
Section: The Use Of Arsenic-based Pigmentsmentioning
confidence: 99%
“…Arjonilla et al [ 139 ] used Raman and FTIR microspectroscopies to reveal medieval Hispano–Muslim wood painting techniques and provide new insights into red lead production technology. Burgio et al [ 140 ] studied orange for gold by the use of arsenic sulfide glass in the Leman Album at the Victoria and Albert Museum. They reported that arsenic sulfide glass was detected in most of the orange areas, thus confirming that this material was popular among silk designers of 18th‐century London.…”
Section: Art and Archaeologymentioning
confidence: 99%
“…A detailed study of the Leman Album, present in the V&A collection (London) is presented by Burgio et al, [40] including the characterization of arsenic sulfide glasses as unusual pigment used as substitutes for orpiment and relagar. The combined Raman, SEM-EDX, XRD study of the mineral phases present in archaeological ceramics coming from Karelia (Russia) allowed Chazhengina et al [41] to determine their firing conditions, in terms of temperature and atmosphere.…”
Section: Cultural Heritage and Archaeometrymentioning
confidence: 99%